The use of complementary and alternative medicine (CAM) for pregnancy related low back and/ or pelvic girdle pain: An online survey. (May 2018) - Hughes, Ciara M.; Liddle, S.D.; Sinclair, Marlene; McCullough, Julie E.M.
Abstract: Low back and pelvic girdle pain (LBPGP) is a common complaint among pregnant women, which increases throughout pregnancy and women use various complementary and alternative medicine (CAM) therapies to manage their pain. Using an online survey, CAM treatments used by pregnant women in the UK and their perceptions of these therapies to relieve LBPGP were investigated. 191 women completed the survey and 70% experienced LBPGP lasting more than one week. Over half of women who sought treatment from a GP or physiotherapist were dissatisfied. 25% of participants used CAM during pregnancy, the most popular being aromatherapy (21%), acupuncture (21%), and reflexology (15%). 81% of women used CAM to manage their LBPGP and 85% found it useful for pregnancy symptoms. Women experience high levels of pain during pregnancy with limited treatment options. Research into effective CAM treatments for LBPGP is required to allow women to make informed decisions regarding treatment options. Highlights: Low back and pelvic girdle pain (LBPGP) increase as pregnancy progresses. Pregnant women do not find physiotherapy useful for LBPGP. Women use CAM during all three trimesters, labour and after birth and find them useful for pregnancy related symptoms. 81% of pregnant women who used CAM did so to reduce LBPGP. The most commonly used CAM treatments during pregnancy are aromatherapy (21%), acupuncture (21%), and reflexology (15%).